The Effect of Open Ended Approach on Problem Solving Ability and Learning Independence in Students' Mathematics Lessons - Nur Alfiani Hafidzah; Zainal Azis; Irvan Irvan (Indonesian Journal of Education and Mathematical Science, 2021)
The purpose of this study is to investigate whether 1) solving mathematical problems between students who take learning with an open-ended learning approach and students who take learning without an open-ended learning approach; 2) the influence of mathematical ability among students who have learning independence high, medium and low; 3) whether the Open-Ended learning approaches and student learning independence there was an interaction of the students' mathematical problem solving ability. This research was Quasi Experimental design The Non-equivalent Post-test Only Control Group Design. This study population throughout the first semester of seventh grade students of MTs Negeri 1 Bandar Rice academic year 2018/2019. A research technique used is purposive sampling with a sample class as a class VII-1 and VII-2 experiment as a control group. The research instrument used was a test description to measure students 'mathematical problem solving and a questionnaire to measure students' learning independence. Analysis of the data in this study is a two-way ANOVA. The results of data analysis 1) there is a mathematical problem solving among students who take the learning with the Open-Ended learning approach with students who take the lesson without learning approach Open-Ended; 2) there is an influence on the ability of mathematical problems between students who have high, medium and low learning independence; 3) there is no interaction between the Open-Ended learning approach and students 'learning independence on students' mathematical problem solving ability.